(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
Precedents 269 and 271 of the Supremo Tribunal Federal (Brazilian Federal Supreme Court) establish that the “mandado de segurança” (writ of mandamus) does not replace the collection action and that its granting does not produce financial effects in relation to a past period. At the time the aforementioned precedents were conceived (1963), only typically condemnatory sentences were considered enforceable judicial titles. Since the advent of Law n. 11.232/2005, however, the civil procedural legislation started to confer executive force also to merely declaratory sentences. It is, therefore, past time to review those summary statements, not only because of the legislative evolution, but also by applying the principle of procedural effectiveness.